2006
DOI: 10.1111/j.1365-313x.2006.02863.x
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinase genes MAP3K ɛ 1 and MAP3K ɛ 2 are required for pollen viability in Arabidopsis thaliana

Abstract: SummaryWe have used reverse-genetic analysis to investigate the function of MAP3Ke1 and MAP3Ke2, a pair of closely related Arabidopsis thaliana genes that encode protein kinases. Plants homozygous for either map3ke1 or map3ke2 displayed no apparent mutant phenotype, whereas the double-mutant combination caused pollen lethality. Transmission of the double-mutant combination through the female gametophyte was normal. Tetrad analysis performed using the Arabidopsis quartet mutation demonstrated that the pollen-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 26 publications
(74 reference statements)
2
39
0
Order By: Relevance
“…Similar male-specific gametophytic lethality has been observed for other Arabidopsis mutants, such as (for example) MAP3Ke knockout mutants (Chaiwongsar et al 2006) and the duo pollen mutants (Durbarry et al 2005). In fact, a large percentage of gametophyte mutants identified in forward screens were defective specifically in the male gametophyte (Boavida et al 2009;Procissi et al 2001;).…”
Section: Discussionmentioning
confidence: 65%
“…Similar male-specific gametophytic lethality has been observed for other Arabidopsis mutants, such as (for example) MAP3Ke knockout mutants (Chaiwongsar et al 2006) and the duo pollen mutants (Durbarry et al 2005). In fact, a large percentage of gametophyte mutants identified in forward screens were defective specifically in the male gametophyte (Boavida et al 2009;Procissi et al 2001;).…”
Section: Discussionmentioning
confidence: 65%
“…We are convinced that the plant SIN-like signaling pathways will provide new insights into plant cell differentiation. Data concerned with both the AtSGP GTPases by Bedhomme et al [5] and the AtMAP3Kepsilon kinases by Chaiwongsar et al [8] revealed two paralogues in Arabidopsis. Functional redundancy in plants introduces an additional level of complexity to the analysis of the SIN-like function [8].…”
Section: Discussionmentioning
confidence: 99%
“…The present number of paralogous genes encoding putative SIN-like elements in A. thaliana might have been reached through various mechanisms, including single gene duplications by short range duplication (AtMAP3Kepsilon1/2), or duplication of the whole genome through polyploidy (AtSGP1/2). Many knock-out mutants for A. thaliana duplicated genes resulting from recent polyploidisation, do not have phenotypical effect, as illustrated by independent T-DNA insertion mutants either for AtMAP3-Kepsilon1 or for AtMAP3Kepsilon2 [8]. The mechanism of compensation is putatively functional redundancy, i.e.…”
Section: Elements Of the Sin And Men Pathways With Orthologues In Plantsmentioning
confidence: 97%
See 1 more Smart Citation
“…Double loss-of-function mutations in MPK3 and MPK6 are embryonic lethal, and MPK4 mutants show a severely dwarfed phenotype (Wang et al, 2007;Qiu et al, 2008). Further upstream, double mutation of MAPKKKe1 and MAPKKKe2 in Arabidopsis is pollen-lethal, but plants containing individual mutations to MAPKKKe1 or MAPKKKe2 show no obvious phenotype (Chaiwongsar et al, 2006). The use of an inducible At-MAPKKKe1 construct in the mapkkke1 mapkkke2 background rescues pollen unviability, but the plants show reduced root length and reduced cell expansion in rosette leaves (Chaiwongsar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%